Determination of truck factors in Costa Rican pavements - Ulloa, Álvaro (2025)
In Costa Rica, many bituminous wearing courses fail due to the stresses imposed by vehicles. This study presents the results of the determination of Truck Factors on eight major roadways in Costa Rica. The research is based on the analysis of vehicle load data and traffic classifications. As general conclusions, the study confirms that the Typical Truck Factors used in Costa Rica underestimate the actual vehicle loads. Furthermore, it highlights the need for effective Vehicle Weight Control.